PERAN AKTIF PEMUDA ERA GLOBALISASI DALAM PEMBANGUNAN DESA MUARA SEMERAH KECAMATAN AIR HANGAT KABUPATEN KERINCI: Ade Nurma Jaya Putra - Nurma Jaya, Ade (Qawwam : The Leader's Writing, 2020)
This study aims to determine the Active Role of Youth in the Era of Globalization in the Development of the Muara Semerah Air Warm Village in Kerinci Regency, using data collection techniques through field studies namely conducting direct interviews with Youth in the Development of the Muara Semerah Air Warm Water Village in Kerinci Regency and literature study by reading documents relating to the problem under study to look for concepts, theories, opinions or findings related to the subject matter. Based on the results of the study, it was concluded, about the Active Role of Youth in the Era of Globalization in the Development of the Muara Semerah Air Warm Village in Kerinci District, the lack of active role of young people in various village activities such as Musrenbang, mutual cooperation, management of the village community, and so forth. Young people are also not involved in the ranks of village administrators, resulting in the estuarine genreta as red as a vacuum, on the other hand genreta also does not carry out activities such as recitation, holding inter-household tournaments, social activities. From these phenomena the researcher has obtained the answer, namely from the results of the study with the interview above, namely the authority of the active role of the globalization era youth in Muara Semerah, the warm water district of Kerinci district which is still very low, due to the lack of active youth in village activities and village government. Involving youth organizations in village development. Here it is clear that inactive youth organizations then become vacuum without any activities and lack of synchronization between village government and youth organizations.